Charqui meats as fermented meat products: role of bacteria for some sensorial properties development - Pinto, Marcos Franke [UNESP]; Ponsano, EHG; Franco, BDGM; Shimokomaki, M. (Elsevier B.V., 2002)
Jerked beef, a derivative of charqui meat, is a cured, salted and dried meat product. The presence of halotolerant bacteria, where Staphylococcus spp. (84.2%) were the predominant species, would act eventually as starter cultures and was followed throughout processing. Jerked beef prepared separately with exogenous S. carnosus and S. xylosus as starter cultures resulted in high proteolysis. Samples prepared with S. xylosus had the highest proteolysis and were preferred by the sensory panel. This research has suggested that jerked beef (and thus charqui meat) prepared under these conditions is a fermented meat product. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: fermented meat products; starter cultures; charqui; jerked beef; sensorial properties